PP46 Screening and Alcohol Brief Intervention in Antenatal Care: A Realist Evaluation. (10th September 2013) - Doi, L; Jepson, R; Cheyne, H
Abstract : Background: In an effort to protect the health and safety of the unborn child, the Scottish Government in collaboration with National Health Services (NHS) Health Scotland implemented screening and alcohol brief interventions (ABIs) in a range of health care settings, including antenatal care setting. Yet while there is strong evidence of the benefits of screening and ABIs in reducing hazardous and harmful drinking among primary care population, evidence of their effectiveness with the antenatal care population is limited. Further, the few studies evaluating screening and ABIs in antenatal care settings have tended to rely on randomised controlled trials which often produce inconsistent findings regarding their effectiveness. Moreover, they do not give adequate account of why the intervention worked or not. Realist evaluation focuses on which aspects of the intervention work for whom, how and under what circumstances. In this study we aimed to use realist evaluation design to increase understanding of the factors likely to influence the effectiveness of the recently implemented screening and ABIs in Scottish antenatal setting, delivered at the first antenatal visit. Methods: The study employed a realist evaluation methodology, where a priori program theories were first identified through systematic reviews and face-to-face policy implementers' interviews data. The program theories were tested and later refined using interviews and focus group data with pregnant women and midwives. The qualitative data was analysed by thematic content analysis. Results: Training and resources provided to midwives improved their skills and confidence. However, as many of the women reported to have reduced or abstained from alcohol in pregnancy, most of the midwives had not subsequently employed the motivational interviewing skills acquired from training. Midwives' confidence therefore decreased leading to missed opportunities to appropriately deliver ABIs to eligible women. Further, it negatively affected midwives' attitudes as they then accorded ABIs low priority in their workload. Lack of adequate rapport at the first antenatal interview also led to women providing socially desirable responses to alcohol consumption questions. Conclusion: As trust-based relationships are essential to effective screening and ABI delivery, delivering them at the first antenatal visit when they are likely to make the most impact, may be particularly challenging and may require adequate motivational interviewing skills. However, the limited number of ABI delivered in antenatal care require that midwives may need on-going support to sustain their motivation and skills in order to ensure benefits for the few pregnant women who are drinking at hazardous and harmful levels.